Autophagy as a main driver on Smith-Lemli-Opitz syndrome - Cardoso, Maria Luís (2018)
Introduction: Cholesterol is an important structural component of cellular membranes and myelin and it was found to play an essential role on embryogenesis and development. In the past most of the scientific investigations concerning this lipid were focused on the consequences of high levels of cholesterol and only a few studies reported the dramatic consequences of low cholesterol levels for cells. In the present investigation we used fibroblasts from Smith-Lemli-Opitz syndrome patients (SLOS) - a metabolic genetic disease affecting the cholesterol biosynthesis pathway - to investigate the consequences of cholesterol deficiency on cell morphology and protein expression. Materials and methods: Morphological studies (MTT test, immunocytochemistry for LC3, MDC and acridine orange coloration as well as electron microscopy) and proteomic analysis (iTRAQ LC /MS-MS) were performed on fibroblasts from SLOS patients and human controls, simultaneously cultivated both on standard conditions and cholesterol depleted media. Results: Morphological studies showed that when endogenous synthesis of cholesterol is inadequate (SLOS) and there is no appropriate supply to overcome cellular needs (cholesterol depleted media), cell proliferation in vitro becomes impaired and autophagy is activated. Once, activation of autophagy, in the absence of cholesterol seems to be a self-rescue mechanism of the cell, we further investigated if there was also changes in protein expression which support surviving cell adaptive modifications. SLOS cells in cholesterol depleted medium show an overexpression of a set of proteins. Mainly, these cells seems to increase MnSOD expression to combat oxidative stress derived from the increased amount of 7-dehydrocholesterol and its derivatives, caused by the inherited enzymatic deficiency and thus control cell proliferation, whereas heat shock 70 kDa protein 4, an autophagic protein (Atg2) also presents a cytoprotective activity and inhibits apoptosis. Conclusion: We conclude that the mechanism by which SLOS fibroblasts handles their metabolic deficit, involves autophagy which plays an important role in cell survival. Furthermore this work provided powerful indications that may be useful to expand the knowledge about the mechanisms involved in cellular pathophysiology of SLOS.